2012
DOI: 10.1007/s11010-012-1250-x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophosphamide-induced nephrotoxicity, genotoxicity, and damage in kidney genomic DNA of Swiss albino mice: the protective effect of Ellagic acid

Abstract: Cyclophosphamide (CPM), an alkylating agent is used as an immunosuppressant in rheumatoid arthritis and in the treatment of several cancers as well. In this study, Ellagic acid (EA), a naturally occurring plant polyphenol, was evaluated for its antigenotoxicity and antioxidant efficacy against the CPM-induced renal oxidative stress and genotoxicity in Swiss albino mice. The mice were given a prophylactic treatment of EA orally at a dose of 50 and 100 mg/kg body weight (b wt) for seven consecutive days before t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
80
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(92 citation statements)
references
References 49 publications
8
80
0
4
Order By: Relevance
“…Chrysin (Pushpavalli et al, 2010, Veerappan andSenthilkumar, 2015), biochanin-A (Zhang et al, 2011) and ellagic acid (Warpe et al, 2015a) are compounds attributed with anti-oxidant properties. There are proven studies of chemoprotective properties of ellagic acid (Rehman et al, 2012, Warpe et al, 2015b. It is hence, conclusive that the presence of anti-oxidant compounds in the OIM extract may possibly have mediated the chemoprotective effects, through their combined action.…”
Section: Discussion:-mentioning
confidence: 95%
“…Chrysin (Pushpavalli et al, 2010, Veerappan andSenthilkumar, 2015), biochanin-A (Zhang et al, 2011) and ellagic acid (Warpe et al, 2015a) are compounds attributed with anti-oxidant properties. There are proven studies of chemoprotective properties of ellagic acid (Rehman et al, 2012, Warpe et al, 2015b. It is hence, conclusive that the presence of anti-oxidant compounds in the OIM extract may possibly have mediated the chemoprotective effects, through their combined action.…”
Section: Discussion:-mentioning
confidence: 95%
“…An oxidative stress was formulated from a disturbance between the generation of reactive oxygen species (ROS) and their elimination through antioxidant systems. The GSH either can be regarded as a non-enzymatic anti-oxidant through interplaying between ROS and SH group or may be implicated in the enzymatic detoxification response for ROS as a cofactor (22). The MDA, an indicator of oxidative damage, increases in body after injection of CP, resulting in the ultimate damage to membrane lipids with the creation and diffusion of free radicals and raised uptake of oxygen, leading to the transformation of the double bonds in unsaturated lipid.…”
Section: Discussionmentioning
confidence: 99%
“…It is a well-known bi-function alkylating agent that transfer alkyl residues into a covalent bond with DNA widely used in cancer chemotherapy and expresses its genotoxicity when metabolically activated (36). Normal tissues injury or damage is the major limitation of using CP, which gives rise to numerous side effects, CP treatment also results in the production of ROS, which cause peroxidative damage to kidney and other vital organ (37). A number of studies has been reported that CP or its metabolites leads to acute inflammation of the urinary bladder (cystitis), renal damage and liver damage, thereby limiting the therapeutic use of the drug (38).…”
Section: Discussionmentioning
confidence: 99%